How the flexibility of human histone deacetylases influences ligand binding: an overview. Issue 6 (June 2015) - Deschamps, Nathalie; Simões-Pires, Claudia Avello; Carrupt, Pierre-Alain; Nurisso, Alessandra
Highlights This review covers the flexibility events occurring within the human zinc-dependent HDACs. The therapeutic importance of the discovery of new HDAC modulators is emphasized. Both mass and one-off movements associated to each HDAC isoform are described and illustrated. Key structural elements for the design of novel HDAC-selective modulators are highlighted. A brief overview on the computational methods used for studying flexibility is given.